Retention Pond Planning for Flood Management Using Epa SWMM in Sayung Village Demak Regency - Ari Sentani; Moh Faiqun Niam (Universitas Islam Sultan Agung, 2023)
The area of Sayung Village, Sayung District, and Demak Regency is an area that is often hit by annual floods. According to the Sayung Village Government, floods in 2019 resulted in 5,884 residents of Sayung Village being displaced and 1,471 houses being flooded. The area of submerged rice fields is 300 hectares, with the number of farmers who failed to harvest reaching 436. Comprehensive handling is needed to deal with the flood. For flood management, a simulation of a flood management system was made with EPA SWMM (Environmental Protection Agency Storm Water Management Model) software. The selection of handling concepts is obtained through re-simulation of the capacity of drainage channels in order to accommodate planned discharge. To be able to perform simulations, hydrological data and measurements of existing channels are needed. Flood discharge obtained from the calculation results is Q2 of 110.1 m3 per second, Q5 of 134.9 m3 per second, and Q10 of 147.8 m3 per second. The handling concept obtained from this study is the creation of retention ponds in Dukuh Sayung Kidul and Dukuh Sayung Wetan.